Інституту мистецтвознавства, фольклористики та етнології ім. М.Т. Рильського НАН України - 85 років - Скрипник, Г. (Матеріали до української етнології, 2007)
This article is devoted to the 85th anniversary of the Rylsky Institute of Art Studies, Folklore, and Ethnology. The author retraces a long and not easy formation route from the art study cells to the leading field institution. Valuation of the science establishment’s activity at different periods of its historical development is also given in the article.